The Epistemology of Ṭarīqa: Reframing Sufi Orders as Systems of Spiritual Education - M. Agus Wahyudi; Ady Muh. Zainul Mustofa; Muhaimin Abdillah; Nur Sidik (LaKaspia, 2026)
This study examines the epistemological foundations of ṭarīqa (Sufi orders) by reconstructing their role as systems of spiritual education within the broader framework of Islamic pedagogy. In modern academic discourse, tarekat are often reduced to mere ritual practices or socio-religious institutions. In contrast, this study argues that tarekat constitute a structured epistemological system that integrates revelation, spiritual experience, and authoritative guidance. Employing a qualitative approach based on library research, alongside conceptual and epistemological analysis, this study investigates both classical and contemporary sources to identify the key components of knowledge production, transmission, and validation within ṭarīqa. The findings reveal that the epistemology of tarekat consists of three interrelated elements: (1) sources of knowledge that are textual, experiential, and authoritative; (2) methods of knowledge acquisition grounded in practice and experiential engagement through ṭarīqa rituals; and (3) mechanisms of validation based on spiritual authority and the continuity of sanad. The learning process within ṭarīqa is inherently transformative, emphasizing the internalization of spiritual values through disciplined practices such as bay‘ah, dhikr, riyāḍah, mujāhadah, and sulūk under the guidance of a murshid. This process reflects a holistic educational model that integrates cognitive, affective, and spiritual dimensions in shaping individual consciousness and character. Accordingly, this study offers a new conceptual framework for understanding tarekat as a transformative system of Sufi education, with significant implications for the development of contemporary Islamic pedagogy.